2024
DOI: 10.3390/insects15030210
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Lemongrass and Star Anise Essential Oils and Their Main Constituent: Synergistic Housefly Repellency and Safety against Non-Target Organisms

Mayura Soonwera,
Jirisuda Sinthusiri,
Hataichanok Passara
et al.

Abstract: The present study evaluated the housefly repellency of single-component formulations and combinations of lemongrass and star anise essential oils (EOs) and their main constituents. The efficacies of the combinations were compared against those of single-component formulations and DEET. Safety bioassays of all formulations and DEET on non-target species—guppy, molly, dwarf honeybee, and stingless bee—were conducted. GC–MS analysis showed that the main constituent of lemongrass EO was geranial (46.83%) and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
(147 reference statements)
0
1
0
Order By: Relevance
“…Thymol was demonstrated to be effective against adult house flies with a synergetic effect when mixed with p-cymene, another main component of thyme oil [ 23 ]. Evaluations were also conducted on essential oils of star anise and lemongrass for their contact toxicity and repellency with no harm to non-target organisms [ 24 , 25 ]. There also are studies that reported insecticidal effects on other dipterans, such as Ceratitis capitata [ 26 ] and Drosophila suzukii [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thymol was demonstrated to be effective against adult house flies with a synergetic effect when mixed with p-cymene, another main component of thyme oil [ 23 ]. Evaluations were also conducted on essential oils of star anise and lemongrass for their contact toxicity and repellency with no harm to non-target organisms [ 24 , 25 ]. There also are studies that reported insecticidal effects on other dipterans, such as Ceratitis capitata [ 26 ] and Drosophila suzukii [ 15 ].…”
Section: Introductionmentioning
confidence: 99%